1988
DOI: 10.1159/000217563
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Estimation of Epidermal Growth Factor Receptors and Steroid Receptors in a Series of 136 Resectable Primary Breast Tumors

Abstract: Human breast cancer cell lines, as well as human breast cancer biopsies, possess specific high-affinity epidermal growth factor receptors (EGF-r). However, reports on the presence of EGF-r in human breast cancer biopsies are still controversial, especially concerning the relationship between EGF-r and other biological variables whose prognostic relevance is well known, such as the estrogen (ER) and progesterone (PgR) receptors. In the present study, the EGF-r content was estimated in a series of 136 unselected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…In addition, Spitzer et al (56) found higher EGF-R levels in larger tumors (>4 cm). In contrast, Cappelletti et al (38) observed that tumors larger than 3 cm were mostly EGF-R-negative, while smaller tumors (<3 cm) were almost equally distributed among the EGF-R-positive and -negative subsets. Bolla et al (50) and our group (41) found a tendency to higher EGF-R levels in Tl tumors when compared to T2 and T3 tumors, respectively.…”
Section: February 1992mentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, Spitzer et al (56) found higher EGF-R levels in larger tumors (>4 cm). In contrast, Cappelletti et al (38) observed that tumors larger than 3 cm were mostly EGF-R-negative, while smaller tumors (<3 cm) were almost equally distributed among the EGF-R-positive and -negative subsets. Bolla et al (50) and our group (41) found a tendency to higher EGF-R levels in Tl tumors when compared to T2 and T3 tumors, respectively.…”
Section: February 1992mentioning
confidence: 88%
“…Bolla et al (50) and our group (41) found a tendency to higher EGF-R levels in Tl tumors when compared to T2 and T3 tumors, respectively. Thus only two (25, 56) of 17 study groups found a positive correlation between tumor size and EGF-R levels, while three others (38,41,50) found a trend toward a negative relationship.…”
Section: February 1992mentioning
confidence: 89%
“…Cytosolic ER and progesterone receptors (PR) were simultaneously estimated by a double-labelling DCC assay as described (Ronchi et al, 1986). Nuclear pellets were salt-extracted as described (Cappelletti et al, 1988), and cytosol and nucleosol were incubated overnight with 16α-[ 125 I]-iodo-oestradiol (8150 GBq mmol -1 , 5 nM), alone or in the presence of a 200-fold molar excess of oestradiol. Incubation was stopped by treatment with a DCC pellet.…”
Section: Steroid Receptor Determinationmentioning
confidence: 99%
“…Cells (200-300 x 106) were homogenized by me chanical disruption to prepare subcellular fractions [16]. IGF-I and EGF receptor (IGF-I-R and EGF-R, respectively) content was determined on the crude nuclear membrane fraction using a radioligand assay as previously described [17], Steroid receptor deter minations were carried out with commercially avail able immunoenzymatic kits (ER-EIA, PR-EIA.…”
Section: Receptor Cathepsin-d Andps2 Determinationsmentioning
confidence: 99%